Public relations information and practices as viewed by women's newspaper editors - Simms, Jayne (My University, 1973)
Contents include: scope and conduct of the study, description of women's departments, use of public relations materials in women's sections of newspapers, use of business recipe releases and free product samples, newspaper policies and attitudes concerning public relations freebies, recommendations for public relations information services, and attitudes towards public relations.
209 leaves ; 29 cm.
Keywords: Women journalists.